Sekularingseringstesen i religionssociologien - Kühle, Lene (Religionsvidenskabeligt Tidsskrift, 1999)
Secularization has been á major issue in sociological debates on religion. Recent developments in theory as well as in social reality seems to indicate that the future for the seularization thesis will not be as glorious as the past. The main argument in this article is that the secularization thesis, which can more properly be understood as a paradigm in the Kuhnian sense, is no longer a very useful frame for the sociological study of religion. This argument is supported by three examples from the contemporay political sphere, where the description in terms of "secularization" seems to lead to ambiguous conclusions. The article gives a brief presentation of two candidates for a new paradigm and discusses the requirements that the new paradigm is expected to meet. Whether any of these paradigms or perhaps a completely different one is going to assume the position as the dominant paradigm in the sociology of religion is still to be seen.